인공지능기술의 IoT 통합보안관제를 위한 데이터모델링 - 오영택(Young-Taek Oh); 조인준(In-June Jo) (한국콘텐츠학회 논문지, 21(12), 2021)
A hyper-connected intelligence information society is emerging that creates new value by converging IoT, AI, and Bigdata, which are new technologies of the fourth industrial revolution, in all industrial fields. Everything is connected to the network and data is exploding, and artificial intelligence can learn on its own and even intellectual judgment functions are possible. In particular, the Internet of Things provides a new communication environment that can be connected to anything, anytime, anywhere, enabling super-connections where everything is connected. Artificial intelligence technology is implemented so that computers can execute human perceptions, learning, reasoning, and natural language processing. Artificial intelligence is developing advanced technologies such as machine learning, deep learning, natural language processing, voice recognition, and visual recognition, and includes software, machine learning, and cloud technologies specialized in various applications such as safety, medical, defense, finance, and welfare. Through this, it is utilized in various fields throughout the industry to provide human convenience and new values. However, on the contrary, it is time to respond as intelligent and sophisticated cyber threats are increasing and accompanied by potential adverse functions such as securing the technical safety of new technologies. In this paper, we propose a new data modeling method to enable IoT integrated security control by utilizing artificial intelligence technology as a way to solve these adverse functions. 산업 전 분야에 4차 산업혁명의 신기술인 IoT(Internet of Things), AI(Artificial Intelligence), Bigdata 등이 융합되어 새로운 가치를 창출하는 초연결 지능정보사회가 도래되고 있다. 모든 것이 네트워크에 연결되어 데이터가 폭발적으로 증가하고, 인공지능이 스스로 학습하여 지적 판단 기능까지도 가능하다. 특히 사물인터넷은 언제 어디서나 어느 것과도 연결될 수 있는 새로운 통신환경을 제공함에 따라 모든 것들이 연결되는 초 연결을 가능케 하고 있다. 인공지능 기술은 인간이 가진 지각, 학습, 추론, 자연어처리 등의 능력을 컴퓨터가 실행할 수 있도록 구현되고 있다. 인공지능은 기계학습, 딥러닝(Deep leearning), 자연어처리, 음성인식, 시각인식 등 첨단기술을 개발하는 방향으로 발전되고 있으며, 안전, 의료, 국방, 금융, 복지 등의 다양한 응용 분야에 특화된 소프트웨어와 머신러닝(Machine learning), 클라우드(Cloud) 기술을 포함하고 있다. 이를 통해 인간의 편의와 새로운 가치를 제공하기 위해 산업 전반의 다양한 분야에 활용된다. 하지만, 이와는 반대로 지능적이고 정교해진 사이버 위협들이 증가하고 신기술의 기술적 안전성 확보와 같은 잠재적 역기능들을 동반함에 따라 이에 대한 대응이 필요한 시점이다. 본 논문에서는 이러한 역기능을 해결하기 위한 하나의 방안으로 인공지능기술을 활용하여 IoT 통합보안관제 가능하도록 새로운 데이터모델링(Data modelling) 방안을 제안하였다.